KERAPATAN DAN BIODIVERSITAS NEMATODA TANAH GAMBUT DI KECAMATAN GAMBUT, KABUPATEN BANJAR, KALIMANTAN SELATAN - Dewi Rahmita; Abdul Gafur; Rusmiati Rusmiati (Bioscientiae, 2007)
Density and biodiversity of soil nematodes at different depths of peat soil were studied in search for optimum depth of soil samples taken for nematode community data. Soil samples were taken from a natural peat land at Gambut Subdistrict, Banjar District, the Province of South Kalimantan, and were separated into 0-5 cm, 5-10 cm, and 10-15 depth groups. Soil nematode density and number of species were recorded along with soil pH, water content, and total-N content. Nematode biodiversity was estimated by sample-based and individual-based species accumulation curves and Shannon-Wiener diversity index. It was demonstrated that 5-10 cm was the optimum depth of soil samples for nematode biodiversity in the study area, despite insignificant difference between 0-5 cm and 5-10 cm in nematode densities. The results suggested that soil samples for nematode community data in peat soils could be taken up to 10 cm deep. It was also demonstrated that ten samples and one thousand individual nematodes were sufficient to obtain representative data on nematode biodiversity in the study area.